ANALISIS TINGKAT MINAT BELI PRODUK SUSTAINABLE FASHION PADA GENERASI Z DI JABODETABEK - Miftahul Jannah Khaerunnisa; Mohammad Rizan; Nofriska Krissanya (Jurnal Riset Multidisiplin Edukasi, 2026)
Sustainable fashion concept has become a global trend. Particularly among Generation Z and Millenials who are more aware with environmental issues. The emergence of this concept is based on concern over negative impact from fast fashion production. This study aim to analyze the level purchase intention Generation Z in Jabodetabek region towards sustainable fashion product by applying Theory of Planned Behavior. The target of this research is Generation Z residing in the Jabodetabek region. The data were colected through an online questionnaire, resulting 123 respondents who met the eligibility criteria. This is quantitative research and this study use purposive sampling methode and applies descriptive analysis techniques using weighted scale and interval scale calculations. The result of this study indicate Generation Z in Jaboedetabek region has high level of purchase intention toward sustainable fashion product. All indicators in Theory of Planned Behavior – Attitude, Subjective norms, and Perceived behavioral control – significantly contribute to shaping Generation Z’s purcahase intention toward sustainable fashion product in Jabodetabek region.